Knowledge, Attitude and Practice of Family Planning Among the Currently Married Women of Reproductive Age of Shivasatakshi Municipality Jhapa District, Nepal - Bista, Sarita Karki (Patan Pragya, 2021)
This study examines the Knowledge, Attitude and Practice of Family Planning among the Currently Married Women of Reproductive Age (15-49 Years); a case study of Shivasatakshi Municipaity Jhapa district is based on primary data successfully collected from sample survey, covering 100 sample respondents` from 100 sample households. The main objective of the study is to fine out the knowledge, attitude and practice of family planning methods among currently married women of reproductive age group (15-49 years) and the specific objective of the study are to study the socio-economic and demographic determinants of currently use of family planning method and to identify the reason the reason for use and non-use of family planning. Out of 100 sample respondents 83 percent women are literate and 17 percent are illiterate. The major occupations of the respondents are agriculture and services. Among currently married women, 99 percent of respondents are found to be familiar with at least one family planning method. Out of total respondents, 91 percents are ever uses and 92 percent are currently using family planning methods. There is strongly positive relationship existed between use of family planning method and socio-economic and demographic variables like educational status of women and number pf living children. Easily accessible and no side effect are main reasons for using family planning method. Desire for and husband and family’s disagreement are most important reason for not using family planning method.